Comprehensive analysis of silk proteins and gland compartments in Limnephilus lunatus, a case-making trichopteran - Rouhova, Lenka; Zurovcova, Martina; Hradilova, Miluse; Sery, Michal; Sehadova, Hana; Zurovec, Michal (BMC genomics, 2024)
Caddisfly larvae produce silk containing heavy and light fibroins, similar to the silk of Lepidoptera, for the construction of underwater structures. We analyzed the silk of Limnephilus lunatus belonging to the case-forming suborder Integripalpia. We analyzed the transcriptome, mapped the transcripts to a reference genome and identified over 80 proteins using proteomic methods, and checked the specificity of their expression. For comparison, we also analyzed the transcriptome and silk proteome of Limnephilus flavicornis. Our results show that fibroins and adhesives are produced together in the middle and posterior parts of the silk glands, while the anterior part produces enzymes and an unknown protein AT24. The number of silk proteins of L. lunatus far exceeds that of the web-spinning Plectrocnemia conspersa, a previously described species from the suborder Annulipalpia. Our results support the idea of increasing the structural complexity of silk in rigid case builders compared to trap web builders.
Keywords: Animals; hedvábí; Limnephilus flavicornis; Fibroin; proteom; Gene duplication; Proteome; Fibroins; proteomika; hmyzí proteiny; stanovení celkové genové exprese; fibroiny; Sericin; Plectrocnemia conspersa; Proteomics; Hydrophobicity; hmyz; transkriptom; Insect Proteins; zvířata; Transcriptome; Silk; Insecta; Gene Expression Profiling